The Role And Strategy Of The Traffic Police Of The Central Java Police To Reduce The Number Of Accidents - Mustiko, Jati (CV. Inara, 2022)
Traffic problems are a problem that often gets the public's attention, because traffic has a very strategic role in supporting development and national integration as an effort to promote public welfare, as mandated in the 1945 Constitution which is part of the national transportation system. The formulation of the problem is what is the definition and form of traffic violations? What are the factors that cause people to violate traffic? What is the role and strategy of the Traffic Police of the Central Java Police in reducing the number of accidents? The type of research used is empirical juridical research or field research, namely examining applicable legal provisions and what is happening in reality in society. Or in other words, a research conducted on the actual situation or real conditions that occur in the community with the intention of knowing and finding the facts and data needed. The conclusion is the role and strategy of the Ditlantas Polda Central Java in reducing the number of traffic accidents includes pre-emptive efforts which are basically in the form of coaching, education on positive activities and socialization about traffic safety for the community, Implementing preventive efforts in the form of controlling, regulating traffic , and monitoring accident-prone lanes, and collaborating with relevant stakeholders such as the Department of Transportation, the TNI, and the Satlantas Polres from the Central Java Regional Police and repressive efforts, namely by enforcing the law for traffic violators in the form of warnings, tickets, fines and confiscation,